Caffeinated – Beverages Consumption Habits and Use among Medical Students in North Jordan - Saadeh, Rami (Jordan Medical Journal, 2019)
Background: Caffeine is the most common used drug in the world. Caffeine usage among college students is known to increase alertness and concentration, as well as to defeat stress and exhaustion. The purpose of this study was to evaluate caffeinated – beverages consumption habits among medical students, especially during examination periods, and reasons for their daily consumption. Methods: This was a cross-sectional study conducted during March 2017 on medical students of two medical colleges in Irbid, Jordan; Jordan University of Science and Technology, and Yarmouk University. A total of 520 students participated in the study. Survey was conducted online and completion of the survey was considered a consent to participate in the study. Descriptive statistics and logistic regression were used in the analysis. Results: Ninety-two percent of students consume caffeine, and 78% reported increased caffeine consumption during exams. Coffee and tea were the most common caffeinated beverages. Reasons for caffeine consumption were to wake more hours during exams (46%), as daily routine (37.5%), to increase concentration (35%), to control stress (19.6%), or as part of norms or traditions (15%). Coffee consumption was a significant predictor for consumption during exams, as a daily routine, to increase concentration, and to control stress. Frequency distribution of demographic information and reasons of consumption were significant in responses to “increase caffeine consumption during exams”. Conclusion: The high percentage of caffeine consumption on a daily basis and during exams among medical students mandates serious efforts to distribute awareness on benefits, side-effects and withdrawal symptoms.